The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/wjo2.78
|View full text |Cite
|
Sign up to set email alerts
|

Cost of open access publishing in otolaryngology‐head and neck surgery

Abstract: ObjectiveOpen access (OA) publishing makes research more accessible but is associated with steep article processing charges (APCs). The study objective was to characterize the APCs of OA publishing in otolaryngology‐head and neck surgery (OHNS) journals.MethodsWe conducted a cross‐sectional analysis of published policies of 110 OHNS journals collated from three databases. The primary outcomes were the publishing model, APC for original research, and APC waiver policy.ResultsWe identified 110 OHNS journals (57 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Open access APCs can cost up to thousands of US dollars [4 ▪▪ ]. Most journals charge less than US $6000 for open access publishing [5]; however, Springer charges authors an APC of US $11 390 to publish open access in Nature and 32 other journals [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open access APCs can cost up to thousands of US dollars [4 ▪▪ ]. Most journals charge less than US $6000 for open access publishing [5]; however, Springer charges authors an APC of US $11 390 to publish open access in Nature and 32 other journals [6].…”
Section: Introductionmentioning
confidence: 99%
“…Different open access journals have varying waiver policies. Kim and Shrime reported that among 98 otolaryngology – head and neck surgery (OHNS) journals reviewed, waivers were offered by only 33.3% [4 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%